SITUATION OF VULVOVAGINAL CANDIDIASIS IN PREGNANT WOMEN IN THE SECOND AND THIRD TRIMESTERS (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of vulvovaginal candidiasis and its associated factors among pregnant women in the second and third trimesters at Dong Nai 2 Hospital. Methods: A cross-sectional study was conducted among 311 pregnant women in the second and third trimesters at Dong Nai 2 Hospital between 2025 and 2026. Participants underwent clinical examination, vaginal pH testing, and wet mount microscopy of vaginal discharge for the diagnosis of candidiasis. Structured interviews were performed to identify potential associated factors.Results: The prevalence of vulvovaginal candidiasis among pregnant women in the second and third trimesters was 28%, with a higher rate observed in those with a gestational age >28 weeks. Factors significantly associated with vulvovaginal candidiasis included low socioeconomic status (OR=12.2; 95% CI: 2.2–16.9), a history of candidiasis (OR=2.2; 95% CI: 1.2–3.9), vaginal douching (OR=2.8; 95% CI: 1.3–5.7), wearing tight underwear (OR=2.4; 95% CI: 1.1–7.9), frequent use of intimate hygiene solutions (OR=2.9; 95% CI: 1.1–7.9), and diabetes mellitus (OR=3.4; 95% CI: 1.1–5.8).Conclusion: The prevalence of vaginal infections among pregnant women was relatively high, particularly in the third trimester. Socioeconomic status, hygiene and lifestyle practices, and diabetes mellitus were associated with vulvovaginal candidiasis. Greater emphasis should be placed on counseling and early identification of risk factors to reduce the prevalence of vulvovaginal candidiasis in pregnant women.
Keywords: vulvovaginal candidiasis; risk factors; pregnant women, the second and third trimesters.